Adherence questionnaire for dietary adaptations in dysphagia - Oriol-Peregrina, Núria (Revista de Investigación en Logopedia, 2018)
Dietary adaptations are adaptive compensation strategies that are used to optimize safety and swallowing efficacy on people who have dysphagia. The aim of the article is to propose an instrument to improve the continuum of care in clinical practice in people with swallowing disorders that require dietary adaptations, given that in the literature there is no instrument of these characteristics. In the design, different methodologies are combined, in which the qualitative and quantitative research approaches are mixed in a single mixed research procedure. The procedure of the Delphi Method is performed to search for consensus in the search for validation evidences based on the content of the items. A total of 13 experts through two rounds arrive at a CVI-I equal to 1 in 100% of the questions presented on the content of the Adherence Questionnaire. The originally proposed instrument is modified and improved thanks to the opinions of the experts. The final result is an Adherence Questionnaire to be used in clinical practice with people suffering from dysphagia and who need adaptations in the diet, agreed by a group of experts.